1988
DOI: 10.1017/s0007485300013213
|View full text |Cite
|
Sign up to set email alerts
|

A field trial of the synthetic oviposition pheromone with Culex quinquefasciatus say (Diptera: Culicidae) in Kenya

Abstract: The synthetic attractant pheromone 6-acetoxy-5-hexadecanolide in a formulation of 20 mg containing 5 mg of the active (-)-(5i?,6S)-isomer in an effervescent tablet produced a high, positive overall response by gravid females of Culex quinquefasciatus Say when the mosquitoes were exposed to the pheromone in established breeding sites in western Kenya. Significantly more females (82%) oviposited around the pheromone source compared to a control. The activity of the pheromone persisted in the established breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 6 publications
2
25
0
Order By: Relevance
“…quinquefasciatus deposited more egg rafts in grass infusion or pheromone than in tap water. Similar observations on the effect of pheromone have been reported by Otieno et al (1988). Strong attraction of Cx.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…quinquefasciatus deposited more egg rafts in grass infusion or pheromone than in tap water. Similar observations on the effect of pheromone have been reported by Otieno et al (1988). Strong attraction of Cx.…”
Section: Discussionsupporting
confidence: 89%
“…(5R,6S)-6-acetoxy-5-hexadecanolide (the synthetic oviposition pheromone, henceforth termed ÔpheromoneÕ) significantly affects oviposition site selection by this mosquito in East Africa (Otieno et al 1988. Recent studies in Muheza, Tanzania, also have indicated that volatiles from soakage pits and grass infusions attract Cx.…”
mentioning
confidence: 99%
See 3 more Smart Citations